Efektivitas penggunaan media literacy cloud.org terhadap minat baca materi paragraf argumentasi kelas iv sekolah dasar - Meliyana Kusumawati; Joko Daryanto; Sandra Bayu Kurniawan (Didaktika Dwija Indria, 2025)
This study aims to measure the effectiveness of using Literacy Cloud.org media on the reading interest of 4th-grade students in argumentative paragraph material for the 2024 academic year. The study employed a pretest-posttest control design, involving an experimental group using Literacy Cloud.org media and a control group using conventional teaching methods. The research sample consisted of 48 randomly selected 4th-grade students. The results showed that the average reading interest of students in the experimental group increased from 69.9 to 86.7 after using Literacy Cloud.org media. The N-Gain test showed an average of 57.8 for the experimental group and 41.32 for the control group, indicating a significant impact from the use of Literacy Cloud.org media. Additionally, the paired sample t-test results showed a significance value of 0.000, which is less than alpha 0.05, indicating a significant difference in reading interest between the pretest and posttest in the experimental group. Thus, the use of Literacy Cloud.org media has proven to be effective in influencing the reading interest of students in argumentative paragraph material.